2020
DOI: 10.1155/2020/2975089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Acute General Surgical Admissions in a District General Hospital in the United Kingdom: A Retrospective Cohort Study

Abstract: The COVID-19 pandemic of 2020 has greatly impacted healthcare systems and society more generally around the world. The management of patients infected with SARS-CoV-2 has primarily impacted emergency departments, medical teams, and intensive care units. However, the impact on health systems as a whole, including surgical specialties, has been wide ranging. We aimed to establish the impact of the COVID-19 pandemic and associated lockdown on the number and characteristics of general surgical patients reviewed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…The findings of our study differ to those seen in multiple UK, Italian and Spanish studies which found large decreases in general surgical admissions, ranging from 14% to 86% 12–18 . Taken in isolation the early intervention period is in line with international literature.…”
Section: Discussionsupporting
confidence: 55%
“…The findings of our study differ to those seen in multiple UK, Italian and Spanish studies which found large decreases in general surgical admissions, ranging from 14% to 86% 12–18 . Taken in isolation the early intervention period is in line with international literature.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, there was no significant difference between the intervals for admissions for peritonitis, acute diverticulitis, bowel obstruction, and acute pancreatitis. The data are reassuring, and support the findings from other units 3 . They confirm that patients with acute surgical conditions requiring immediate review were identified correctly and referred despite the current pandemic, allaying fears that the repeated advice to avoid hospitals might even have deterred patients with life-threatening pathologies.…”
supporting
confidence: 83%
“…In fact, a study from the UK found a reduction in nonurgent surgical admissions following lockdown compared to the year prior. 2 Explanations for reductions in nonurgent admissions might include an increased threshold for patient admission during the…”
Section: Discussionmentioning
confidence: 99%